High maternal iron status, dietary iron intake and iron supplement use in pregnancy and risk of gestational diabetes mellitus: a prospective study and systematic review. Issue 9 (12th January 2016) - Khambalia, A. Z.; Aimone, A.; Nagubandi, P.; Roberts, C. L.; McElduff, A.; Morris, J. M.; Powell, K. L.; Tasevski, V.; Nassar, N.
Abstract: Aim: High iron measured using dietary intake and biomarkers is associated with Type 2 diabetes. It is uncertain whether a similar association exists for gestational diabetes mellitus. The aim of this systematic review was to conduct a cohort study examining first trimester body iron stores and subsequent risk of gestational diabetes, and to include these findings in a systematic review of all studies examining the association between maternal iron status, iron intake (dietary and supplemental) and the risk of gestational diabetes. Methods: Serum samples from women with first trimester screening were linked to birth and hospital records for data on maternal characteristics and gestational diabetes diagnosis. Blood was analysed for ferritin, soluble transferrin receptor and C–reactive protein. Associations between iron biomarkers and gestational diabetes were assessed using multivariate logistic regression. A systematic review and meta‐analysis, registered with PROSPERO (CRD42014013663) included studies of all designs published in English from January 1995 to July 2015 that examined the association between iron and gestational diabetes and included an appropriate comparison group. Results: Of 3776 women, 3.4% subsequently developed gestational diabetes. Adjusted analyses found increased odds of gestational diabetes for ferritin (OR 1.41; 95% CI 1.11, 1.78), but not for soluble transferrin receptor (OR 1.00; 95% CI 0.97, 1.03) per unit increase of the biomarker. Two trials of iron supplementation found no association with gestational diabetes. Increased risk of gestational diabetes was associated with higher levels of ferritin and serum iron and dietary haem iron intakes. Conclusions: Increased risk of gestational diabetes among women with high serum ferritin and iron levels and dietary haem iron intakes warrants further investigation.